Pengolahan Daging Buah Kelapa Menjadi Virgin Coconut Oil (VCO) - Shintia Nabila Putri; Desy Kurniawati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Virgin Coconut Oil (VCO) is a high-quality coconut oil that is extracted from fresh coconut meat without the use of high heat or chemicals, preserving its natural nutrients and beneficial properties. The demand for VCO has increased in recent years due to its various health benefits, such as boosting the immune system, improving digestion, and providing antimicrobial effects. The oil is rich in medium-chain fatty acids, particularly lauric acid, which is known for its positive effects on cholesterol levels and cardiovascular health. This study focuses on the production of VCO using a natural fermentation method, a traditional technique that is gaining attention for its simplicity and environmental friendliness. In this method, mature coconut meat is grated and squeezed to extract the coconut milk, which is then fermented at room temperature for 24–48 hours. The fermentation process allows the separation of the oil from the milk, forming a clear oil layer on top, which retains the characteristic aroma of coconut. The quality of the produced VCO was analyzed by determining its acid value and saponification number. The saponification value, which indicates the amount of alkali required to saponify the fat, was found to be 50.49. The acid value, which reflects the free fatty acid content, was measured at 5.61. These results suggest that the VCO produced through natural fermentation is of relatively good quality, with a favorable acid value indicating lower rancidity. Overall, the study demonstrates that natural fermentation is an efficient, eco-friendly, and cost-effective alternative for VCO production. This method not only preserves the natural properties of the coconut oil but also offers a sustainable approach to producing high-quality oil for various health and cosmetic applications.